SYNTHESIS OF NICKEL OXIDE (NIO) NANOPARTICLES VIA ETHYLENE GLYCOL (EG) ROUTE AND PRELEMINARY STUDY THEIR APPLICATION IN THE VISCOSITY REDUCTION OF HEAVY OIL - PRAWISTIN NOORLAILY (NIM : 10208089); Pembimbing I : Dr. Eng. Ferry Iskandar ; Pembimbing II : Pr,
In this research, we use nickel oxide (NiO) for catalyst in viscosity reduction of heavy oil using aquathermolysis reaction. NiO was synthesized by Ethylene Glycol (EG) route. In this method, NiO was prepared by using NiCl2Ã‚Â·6H2O as precursor, EG as solvent and aglomeration preventing agent, and ammonium bicarbonat as precipitant. There are three paramater investigated, i.e. calcination temperature, precursor concentration, and utilization of microwave. In the effect of calcination temperature, as-synthesized NiO was heated between 300oC and 500oC for 1.5 hours. The experimental result showed that crystallite size of NiO are 4.77 nm, 9.08 nm, and 15.26 nm when calcination temperature were 300oC, 400oC, and 500oC. It was cleared that when calcination temperature was increased, the crystallite size of NiO increased. Another effect which being investigated in this paper was effect of precursor concentration. By using different concentration, 0.25 M, 0.5 M and 1 M, crystallite size increase with the concentration as 17.43 nm, 15.67 nm, and 24.79 nm. These result implied that crystallite size of NiO powder can be controlled not only with the calcination temperature but also with prekursor concentration. The last effect which being investigated was effect of microwave-assisted in synthesis NiO. In usual process of synthesis, the as-synthesized NiO was stirred and heated on 80oC in 30 minutes for completed the reaction. But in effect of microwave-assisted, the as-synthesized was heated in microwave only in 5 minutes. The result showed that using microwave-assisted, synthesis NiO can completed in less time. After NiO has been succesfully synthesized, this NiO was applied in catalyst for aquathermolysis process used for the viscosity reduction of heavy oil. Heavy oil, water, and NiO was mixed then heated on 120oC in autoclave for 6 hours. After that the viscosity of heavy oil was measured and the catalytic of NiO was be discovered.